A planning model for the optimisation of the end-of-life vehicles recovery network. Issue 4 (1st January 2014) - Mora, Cristina; Cascini, Alessandro; Gamberi, Mauro; Regattieri, Alberto; Bortolini, Marco
European Directive 2000/53 on end-of-life vehicles (ELVs) introduced new constraints, regulations and recommendations on the vehicle design, waste disposal and take-back policy. Automotive original equipment manufacturers (OEMs) are even more involved in the expected vehicle recovery network modifications. As a consequence, one of the most critical and challenging issues for reverse logistics (RL) management is the development of effective tools to support strategic, tactical and operational decisions to yield the maximum economic benefit in compliance with the reference regulations. In this paper, a mixed integer linear programming (MILP) model for ELV closed-loop network design is proposed. The network cost minimisation objective function, the integration of forward and reverse logistics and the inclusion of remanufacturing activities for vehicle module reuse represent the model key features. The proposed model is, further, applied on a realistic Italian case-study and the results of a sensitivity analysis are presented to identify the parameters most affecting the model outcomes.